The age of entitlement : America since the sixties - Caldwell, Christopher (Simon & Schuster, 2020)
"A sweeping 50-year history of how the Baby Boomers took the reforms of the 1960s too far, leading to a multitude of contradictions in American society and values that caused our current political polarization"--